Fan Activism: K-Pop Fans Movement in Thailand’s 2020 Protests - Dewi, Putu Ratih Kumala (UIN Sunan Ampel Surabaya, 2023)
Fans of Korean pop music, known as K-Popers, are not only famous for their preference for music and idol artists, but also for their social movements. K-Pop fans can form social movements that can mobilize the resources they have to attract public sympathy to participate. As well as its massive social movement actions because it is distributed through virtual media and is not only concentrated in one area, but is carried out across national borders. Social movements by K-Popers also continue into the political sphere. One of them is the involvement of K-Popers in political protests in Thailand in 2020. K-pop fans are emerging as a powerful political force in Thailand's anti-government movement. Massive demonstrations took place demanding major political changes. The growing pro-democracy movement is calling for the resignation of Prime Minister Prayuth Chan-ocha, called for curbs on the king's powers, demanding constitutional amendments, new elections and an end to the harassment of rights activists and state critics. This paper aims to explain how K-Popers is involved in the rejection movement in Thailand in 2020.This paper uses a qualitative research method. The data used in this paper comes from secondary sources such as government official web- sites and international media coverage. By using the concept of social movement, new social movement theory and cyberactivism, the author finds that K-Popers utilize social media in their movements. Politics is not their main focus but social care and solidarity that makes them move together.